(untitled) (Web of Teachers: Inderscience Research, 2025)
As a an English teacher, I have seen many talented young boys and girls who can acquire a new language so quickly and they are all are excellent at others subjects, too. However, when you investigate their family roots, many of their parents are bilingual or multilingual. In Central Asia many the nations have been living in harmony for thousands of years. They may be Tadjik, Uzbek, Kazakh, Kyrgiz, Uygur, Turkmen, Russian, Belorus, or even ethnic German. They all can speak uzbek and their own language. And their children are mostly very good at learning. Their critical thinking and cognitive development is extraordinarily surprising. Not only that but also, their problem-solving skills are amazing.